ANALISIS EFISIENSI DAN KELAYAKAN FINANSIAL USAHATANI PADI DENGAN SISTEM SALIBU - Anam, Khoirul; Mulyono, Joko Sri; Effendi, Fachri Naufal (Berkala Ilmiah AGRIDEVINA, 2021)
This study aims to analyze the level of efficiency and financial feasibility of salibu rice farming compared to conventional systems of rice farming. The research was conducted in May - July 2018 with a total sample of 5 farmers using the Salibu system and 5 farmers using the conventional system. The data collected is primary data obtained through direct interviews with respondents and secondary data obtained from the local sub-district office and from related offices. Data analysis methods include analysis of costs, revenue and income of farming, as well as farm efficiency analysis with R / C ratio and analysis of farm financial feasibility with B / C ratio. The results showed that the fixed costs and variable costs of rice farming in the Salibu system were lower than the conventional system. The amount of revenue and income from the Salibu system of rice farming shows a higher value than the conventional system. Based on the calculation of R / C ratio and B / C ratio, it is shown that the salibu system is more efficient and more feasible to run than the conventional system. Testing through the T test proves that there is a significant difference between the income of rice farming in the Salibu system and the conventional system. DOi : https://doi.org/10.33005/adv.v10i1.2574